Clinical Features and Post-Coiling Outcomes of Symptomatic Internal Carotid Artery–Posterior Communicating Artery Aneurysms: A Case Series and Literature Review - Wajima, Daisuke; Kamide, Tomoya; Nakada, Mitsutoshi (Asian Journal of Neurosurgery, 2025)
This article aims to understand the clinical course of symptomatic internal carotid artery (ICA)–posterior communicating artery (PCom) aneurysms and the outcomes of post-coiling for unruptured symptomatic aneurysms by analyzing the anatomical imaging data and patient backgrounds of patients treated in our institute in the last 5 years.This study enrolled 82 patients with ICA-PCom aneurysms. Anatomical factors, including age, sex, side, aneurysm dome and neck size, aneurysm depth/neck width ratio (ASPECT ratio), family history of cerebral aneurysm, history of hypertension, smoking habit, angle between aneurysm dome protrusion and ICA C2 portion, angle between ICA C2 and C3 portions, and PCom diameter, were analyzed. In the outcome analysis of coil embolization for symptomatic unruptured ICA-PCom aneurysms, we evaluated age, sex, side, aneurysm dome and neck side, ASPECT ratio, volume embolization ratio, and time from onset.Mann–Whitney U and Fisher's exact tests were utilized for quantitative and categorical variables, respectively.In both ruptured and unruptured ICA-PCom aneurysms, the angle between the aneurysm dome protrusion and ICA C2 portion and the angle between the ICA C2 and C3 portions were smaller in the oculomotor palsy group than in the nonoculomotor palsy group. Other factors such as age, sex, side, aneurysm dome, neck, ASPECT ratio, family history, hypertension, smoking, and PCom diameter did not significantly influence oculomotor palsy. Early coil embolization led to better recovery of neural function, with immediate intervention offering the highest chance of full recovery.Overall, this study showed that sharp ICA siphon and aneurysm dome protrusion are significant factors in symptomatic ICA-PCom aneurysms. We propose that immediate surgery be recommended for patients with ICA-PCom aneurysm-induced oculomotor nerve palsy to prevent functional disability and potential aneurysm rupture.
Keywords: internal carotid artery–posterior communicating artery aneurysm; internal carotid artery siphon; aneurysm dome protrusion; oculomotor nerve palsy; angle